041 'Big room' – improvements through better listening and collaboration. (December 2018) - Stojanovic, J; Baugh, N; Hoskins, S; Pilkington, C; Katugampola, H; Soar, D; Hothi, D
Abstract : Introduction: The combined and unceasing efforts of healthcare professionals, patients, families, researchers, payers and educators in making changes that lead to better patient outcome, better system performance and better professional development are defined as quality improvement (Batalden and Davidoff, Qual Say Health Care.2007 Feb).The concept of 'Big Room' was introduced to aid improvements: the idea being that by seeing the system together, we learn and act together to make improvements (The Flow Coach Academy;sheffieldmca.org.uk).The 'Big Room' supports collaborative behaviour of multidisciplinary teams and is flexible, practical and has visual information. Method: In 2018, as part of Quality Improvement, the 'Big room' was introduced in three services at Great Ormond Street Hospital: Nephrology, Endocrinology and Rheumatology. To date, all three projects are running. Big Rooms are held weekly, last one hour and are facilitated using effective meeting skills. Results: Department of Nephrology held 13 Big Rooms since the start of project in March 2018. Meetings are mostly attended by nurses, consultants and junior doctors. The team rapidly advanced work on dialysis pathway in a relatively short time period due to the collective brainpower in the room. The agenda is circulated in advance of the meeting to ensure that all team members are prepared for more effective discussions. Ground rules are flagged at the beginning of each meeting. There is positive reinforcement, high energy, dynamic and challenging atmosphere conducted in a non hierarchal way. We use visual aids on walls to keep team informed of progress. Feedback is collected at each meeting and analysed by Coaches. The feedback so far has been very positive some of which includes: 'people encouraged to speak and give their opinion', 'there is no hierarchy which is great', 'everyone's opinion is listened to'. Conclusion: Use of 'Big Room' improves collaboration through greater team integration. It enables teams to better understand challenges in service, reduces rework and leads to more effective delivery of quality improvement.